Prevalence of Toxoplasmosis in Feral Cats at Pasuruan Traditional Markets: Prevalensi Toksoplasmosis pada Kucing Liar di Pasar Tradisional Pasuruan - Ferliantono Pratama; Syahrul Ardiansyah (Academia Open, 2023)
General background: Feral cats, as definitive hosts, play a key role in spreading T. gondii in human environments. Specific background: Traditional markets, with their poor sanitation, provide ideal conditions for toxoplasmosis transmission. Knowledge gap: Little is known about the prevalence of toxoplasmosis in feral cats in Pasuruan's markets. Aims: This study aimed to identify T. gondii in feral cats from Pasar Pandaan and Pasar Kepulungan. Results: Prevalence rates were 40% in Pasar Pandaan and 20% in Pasar Kepulungan, with sanitation likely affecting the results. Novelty: The study is one of the first to assess T. gondii in Pasuruan’s markets. Implications: Improved sanitation could reduce the transmission of toxoplasmosis from cats to humans. Highlights: Feral cats in traditional markets are potential carriers of T. gondii, with a prevalence of 40% in Pasar Pandaan and 20% in Pasar Kepulungan. Sanitation quality in markets significantly affects the spread of toxoplasmosis, with cleaner environments showing lower infection rates. Public health measures, including improved market hygiene, are essential to reduce the risk of toxoplasmosis transmission to humans. Keywords: Toxoplasmosis, Cats, Felis Silvestris, Markets, Ookista T.gondii